Awareness and perception of contact lens usage and refractive surgery among first year undergraduate medical students - Palani, Maanasa; Ravi, Shruthi; Puri, Sanjeev Kumar (International Journal of Research in Medical Sciences, 2022)
Background: Refractive error occurs when the parallel rays of light coming from infinity are focused either in front or behind the retina, in one or both the meridians resulting in blurred image. The purpose of this study is to assess the level of awareness and perception of contact lens usage and refractive surgery among first year undergraduate medical students. Methods: A cross sectional, observational questionnaire-based study was done on students studying in Saveetha medical college near Sriperumbudur between February 2021 to April 2021 to assess student’s awareness and perception of contact lens usage and refractive surgery. Results: Totally 250 students were studied, of which 39.76% were under 20 years, 61.85% are not contact lens users, 51.41% think that appropriate time of wearing contact lens was 8 hours per day, 64.66% think that soft contact lens should be used, 70.28% think that contact lens should be renewed every 3 months, 38.96% are not aware of refractive surgery, 54.62% think that dry eye is the complication of long term usage of contact lens, 44.18% think that contact lens are required even after surgery, 38.55% think that there will be complications even after refractive error surgery. Conclusions: The awareness of knowledge, attitude and practice regarding contact lenses usage and refractive surgery was evaluated among the participants to identify the points of weakness and construct a proper health education among the students.